Eastern Thinkers and Scientists of Uzbekistan’s Family Relations and Views of the Causes of Conflict - S., Karimova M. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides а theoretical аnаlysis if the views of Eastern thinkers and Uzbek scholars on family relations and the causes of conflict.